Identifying multipolar acoustic sources by the direct sampling method. Issue 5 (3rd April 2020) - Bousba, Sara; Guo, Yukun; Wang, Xianchao; Li, Longsuo
ABSTRACT: This paper concerns the direct sampling method for solving the inverse problem of identifying point sources for the Helmholtz equation from far-field data. We develop some novel indicator functions which could determine the locations and intensities of the target multipolar sources with a single wavenumber. Theoretically, the indicating behaviors are rigorously analyzed. Two- and three-dimensional numerical experiments are conducted to illustrate the effectiveness and robustness of the proposed approach.